2010
DOI: 10.1016/s0027-9684(15)30471-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes: Descriptors of Nociceptive and Neuropathic Pain and Barriers to Effective Pain Management in Adult Outpatients With Sickle Cell Disease

Abstract: Despite frequent episodes of severe recurrent pain in sickle cell disease (SCD), sensory pain in outpatient adults with SCD lacks sufficient characterization. Furthermore, pivotal barriers may interfere with these patients’ adherence to prescribed analgesic therapies, but have not been studied systematically. We describe sensory pain characteristics, barriers, and analgesic use reported by adults with SCD during routine clinic visits. Patients (N=145, 67% female, 94% African American) completed measures on a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
198
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(210 citation statements)
references
References 44 publications
9
198
1
2
Order By: Relevance
“…Amanda, et al found that almost 40% of SCD study population had evidence of neuropathic pain [19]. Although the underlying pathobiology of SCD pain is not well known [24,25]. Neuropathic pain is shown to be associated with higher pain intensity and longer duration, it is harder to treat, and is more refractory to conventional analgesics [26].…”
Section: Types Of Painmentioning
confidence: 99%
“…Amanda, et al found that almost 40% of SCD study population had evidence of neuropathic pain [19]. Although the underlying pathobiology of SCD pain is not well known [24,25]. Neuropathic pain is shown to be associated with higher pain intensity and longer duration, it is harder to treat, and is more refractory to conventional analgesics [26].…”
Section: Types Of Painmentioning
confidence: 99%
“…A computerized multidimensional pain assessment tool, PAINReportIt ® [2,26,27] (Nursing Consult, LLC, WA, USA), was used for pain phenotyping. Subjects completed baseline pain location, intensity, quality and pattern during a routine clinic visit (i.e., not during pain crisis or other urgent care visits to the clinic).…”
Section: Assessment Of Chronic Painmentioning
confidence: 99%
“…Pain is prevalent and severe in patients with sickle cell disease (SCD), an inherited hematological disorder caused by substitution of a valine residue for glutamic acid in the 6th codon of the β-globin gene [1][2][3]. Although the genetic basis of the disease is well defined, the pathogenesis and heterogeneity of pain in SCD remains poorly understood.…”
mentioning
confidence: 99%
See 2 more Smart Citations